Improving Vegetable Diversity and Micronutrient Intake of Nigerians Through Consumption of Lesser Known Silk Cotton (Ceiba pentandra) Leaf - ADEPOJU Oladejo Thomas; UGOCHUKWU Ihuoma Chinonyerem (International Journal of Nutrition, 2019)
The potential of Nigerian indigenous tree leaves as vegetable source, pharmaceuticals and other therapeutic materials have been reported. However, Silk cotton (Ceiba pentandra) leaf is still underutilised as vegetable in parts of Nigeria where it exists despite its potential great health benefits. The aim of the study was to assess the micronutrient and phytochemical potential contribution to nutrient intake of its consumers, and acceptability of its cooked soup and sauce ‘as consumed’. Fresh young shoots and leaves of Ceiba pentandra were harvested from Ihitte/Uboma in Imo State, Nigeria. Composite sample of the leaf was prepared and divided into four portions. One portion was labelled as raw sample, and others blanched, cooked to soup and sauce. The four samples were analysed for proximate, minerals, vitamins and phytochemical composition using standard methods of AOAC. Sensory evaluation of soup and sauce was carried out using 9-point hedonic scale with 30 untrained panelists. Data were analysed using ANOVA at p<0.05 Raw Ceiba pentandraleaf contained 80.9g moisture, 3.9g protein, 0.8g fat, 15.3g carbohydrate, 68.40 kcal gross energy, 183.40mg potassium, 119.38mg calcium, 112.99mg phosphorus, and 3.46mg iron/100g sample. The leaf was rich in phytochemicals such as saponins, flavonoid and alkaloids. Raw sample was highest in water-soluble vitamins while the sauce was highest in β-carotene (339.72µg/100g). Cooking the leaf to soup and sauce significantly increased the mineral content of the products (P<0.05) with reduction in water-soluble vitamins and phytochemicals (P<0.05). The sensory attributes of the soup and sauce were generally acceptable to the panelists, with the sauce being more acceptable. The leaf and its products were rich in essential minerals, vitamins and phytochemicals. The sauce retained more nutrients compared to other samples. Inclusion of this underutilised vegetable in diets will reduce micronutrient malnutrition, promote dietary diversity, good health and wellness.
Keywords: Ceiba pentandraleaf